2017
DOI: 10.1111/wej.12283
|View full text |Cite
|
Sign up to set email alerts
|

State of SuDS delivery in the United Kingdom

Abstract: Sustainable drainage systems (SuDS) have become a key tool in the design of water sensitive cities, due to their capacity to store and attenuate surface water, and to treat runoff. SuDS implementation requires a complex alignment of planning frameworks, engineering designs, construction practices, maintenance processes, community buy-in and ownership agreements. To understand this alignment, and build an evidence base on the implementation and management of UK SuDS, a questionnaire was distributed to 50 000 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 8 publications
(9 reference statements)
1
39
0
Order By: Relevance
“…Dolowitz et al (2018, p. 85) claimed that '(m)ost Local Authorities now recommend SuDS through the development planning process, but enforcement is constrained by the lack of implementation of national policy relating to SuDS and new developments' (Dolowitz et al, 2018, p. 85). The recent survey of 541 water professionals in the UK further reported the lack of clear national level rules and methodologies for SuDS adoption, uncertainty around costs of maintenance, poor capacity of local authorities, and poor monitoring and enforcement of SuDS as major barriers to implementation (Melville-Shreeve et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dolowitz et al (2018, p. 85) claimed that '(m)ost Local Authorities now recommend SuDS through the development planning process, but enforcement is constrained by the lack of implementation of national policy relating to SuDS and new developments' (Dolowitz et al, 2018, p. 85). The recent survey of 541 water professionals in the UK further reported the lack of clear national level rules and methodologies for SuDS adoption, uncertainty around costs of maintenance, poor capacity of local authorities, and poor monitoring and enforcement of SuDS as major barriers to implementation (Melville-Shreeve et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent survey of 541 experts affiliated with the Chartered Institute of Water and Environmental Management (CIWEM), Melville-Shreeve et al (2018) reported that SuDS implementation in the UK lags behind some other countries. Melville-Shreeve et al (2018) also stressed the lack of data on prevalence of SuDS in the UK and called on professional bodies to produce surveys of existing SuDS schemes (Melville-Shreeve et al, 2018, p. 10). We are interested to understand whether the current lack of an effective institutional framework for SuDS in England prevents the emergence of bottom-up initiatives through collaborative efforts of local authorities, water companies, real estate developers and other actors.…”
Section: Flood Risk Management and Sustainable Urban Drainage Systemsmentioning
confidence: 99%
“…Moreover, recycling other water, such as rainwater or grey water, also provides additional and significant input on a local level [45]. However, this practice is also carried out in countries with other water problems through the use of rainwater harvesting or sustainable urban drainage systems (SuDS), increasing the resilience of the system and mitigating floods, as occurs in the United Kingdom [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, to achieve this objective, a legal framework is required to regulate the use and the implementation of grey water and storm water reuse systems, both on a European level and on a national or regional level, which does not exist at present. water problems through the use of rainwater harvesting or sustainable urban drainage systems (SuDS), increasing the resilience of the system and mitigating floods, as occurs in the United Kingdom [46]. Although the reuse of wastewater is considered to be measure with the greatest potential, recycling other waters such as grey water and rainwater is also worthwhile, because on a smaller scale this can promote the overall use of available water resources and the sustainable management of the resource.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the current focus is on creating an integrated SuDS and conventional drainage approach. Although evidence supports the benefits of SuDS [24,31,44,46,47], there remains an issue in the UK regarding its ownership and ultimately who should be maintaining the systems [48,49].…”
Section: Sustainable Drainage Systems: Pluvial Flooding and Managemenmentioning
confidence: 99%